E-Commerce Sebagai Sebuah Sistem Sosial - Utama, Ditdit N. (Lembaga Penerbitan Universitas Esa Unggul, 2006)
Internet is one space in the sky that can be used to communicate to each others, of course by using Information Technology tools and devices. One of some facilities thatÃ‚Â offered by internet is eCom-merce. ItÃ¢â‚¬â„¢s Internet based Information Technology Facility that allows customers or users can do buying and selling transaction activities. On the other hand, eCommerce can change commu-nication culture, mind set and life style, in these aspects can be called by Social System.Keywords: Internet, eCommerce, Social System